Hubungan Konsumsi Air Jahe Dengan Mual Muntah Pada Kehamilan Di Puskesmas Kebayakan Kabupaten Aceh Tengah Tahun 2021 - Marlina L Simbolon; Mediana Br Sembiring; Edy Marjuang Purba; Rismalia Tarigan; Herni Maulina Azhar (LPPM STIKES Siti Hajar dan Insight Power, 2022)
In Indonesia, as many as 50%-75% of pregnant women experience nausea and vomiting in the first trimester or early pregnancy. Efforts to reduce the frequency of vomiting can be given several actions such as drugs, in addition to drugs, nausea in early pregnancy can be reduced by using complementary therapies such as herbal plants such as ginger. This study aims to analyze the relationship between ginger water consumption and nausea and vomiting in pregnancy at the Kebayakan Public Health Center, Central Aceh. This type of research is a quasi-experimental using a cohort design. The sample was divided into two groups, namely the intervention group and the control group. The population of this study were all pregnant women with nausea and vomiting as many as 30 people in the Kebayakan Health Center, Aceh Tengah Work Area. The number of samples as many as 30 pregnant women who were taken by the accidental sampling technique. The analysis to see the relationship of the independent variable, namely the consumption of ginger boiled water with nausea and vomiting in pregnancy using the mean whytney test with. Percentage of mild nausea and vomiting in the intervention group (86.6%) while the control group (33.3%). There is a relationship between consumption of boiled ginger water with nausea and vomiting in pregnant women at the Kebayakan Health Center, Central Aceh Regency in 2021, with a p value of 0.0013. It is recommended to the Puskesmas Puskesmas to conduct health education in determining the right strategy to overcome nausea and vomiting in pregnant women by consuming ginger water. Keywords: ginger water, nausea and vomiting, pregnant women